Treatment of community-onset methicillin-resistant Staphylococcus aureus (MRSA) bacteremia: A hospital-based study - Chen, Liang-Yu; Chen, Liang-Kung; Chang, Chih-Wei; Kuo, Shu-Chen; Li, Lee-Fang; Chan, Yu-Jiun; Wang, Fu-Der (Archives of Gerontology and Geriatrics, 2012)
S. aureus bacteremia (SAB) is a severe systemic illness, which is associated with high mortality and healthcare cost. It has been reported that older age per se is a poor prognostic factor of SAB, but little is known whether poor clinical outcomes is related to conservative attitudes of treating physicians. A retrospective cohort of 126 patients (mean age: 73.7±13.6years, 72.2% males) with community-onset SAB during 2004–2008 in a tertiary medical center in Taiwan was obtained for study. Demographic data, clinical characteristics, primary infectious focus, metastatic lesions, access to critical care units, performance of invasive procedures, Charlson comorbidity index (CCI) and in-hospital mortality for all study subjects were collected. The overall in-hospital mortality was 32.5%, which was not significantly different between adult and elderly groups. SAB of elderly patients was more likely to be primary than that of the adult patients (20.4% vs. 3.6%, p=0.043). Deep-seated abscess, osteomyelitis and metastatic lesion with central nervous system (CNS) involvement were more common infection foci in the adult patient group. Chronic obstructive pulmonary disease and cerebrovascular accident were more common underlying conditions of the elderly group. Chances of patients admitted to intensive care unit and employment of invasive procedures were not different between groups although elderly patients were supposed to be of a greater risk of mortality. In conclusion, the overall in-hospital mortality of community-onset SAB was 32.5%, which was not different between age groups. In general, older patients were of similar chance to receive critical care and invasive procedures except arterial line and non-tunneled central venous catheters. Further prospective investigation is needed to clarify whether physicians hold different attitudes to older patients with SAB and the differences in treatment attitude resulting in poorer clinical outcomes.